Circularly Polarized Luminescence of Achiral Carbon Dots in Bi‐Solvent Systems Triggered by Supramolecular Self‐Assembly. Issue 68 (5th October 2022) - Zhang, Zhiwei; Yang, Chujing; Dai, Yankai; Zhang, Xinying; Chen, Jingqi; Feng, Lingyan
Abstract: An innovative strategy for circularly polarized luminescence (CPL) of carbon dots (CDs) has been developed: The achiral CDs displayed contrary supramolecular chirality and opposite CPL in two different bi‐solvent systems, which are due to the formation of self‐assembled helical nanostructures with two diverse assembly modes (P and M) in aggregate state via intermolecular π‐π interactions and differential hydrogen bonding (H‐bonding) without the need of any additional element of chirality. Abstract : Supramolecular self‐assembly in bi‐solvent systems has been demonstrated as an unprecedented strategy to realize circularly polarized luminescence of achiral carbon dots. Dissymmetry factors of 10 −3 are obtained in solution, without the need of any additional element of chirality.